Phylogenetic diversity of microorganisms in subseafloor crustal fluids from Holes 1025C and 1026B along the Juan de Fuca Ridge flank - Jungbluth, Sean; Lin, Huei-Ting; Cowen, James; Glazer, Brian T.; Rappe, Michael (Frontiers in Microbiology, 2014)
To expand investigations into the phylogenetic diversity of microorganisms inhabiting the subseafloor biosphere, basalt-hosted crustal fluids were sampled from Circulation Obviation Retrofit Kits affixed to Holes 1025C and 1026B along the Juan de Fuca Ridge flank using a clean fluid pumping system. These boreholes penetrate the crustal aquifer of young ocean crust (1.24 and 3.51 million years old, respectively), but differ with respect to borehole depth and temperature at the sediment-basement interface (147 meters and 39 ºC vs. 295 meters and 64 ºC, respectively). Cloning and sequencing of PCR-amplified small subunit ribosomal RNA genes revealed that fluids retrieved from Hole 1025C were dominated by relatives of the genus Desulfobulbus of the Deltaproteobacteria (56% of clones) and Candidatus Desulforudis of the Firmicutes (17%). Fluids sampled from Hole 1026B also contained plausible deep subseafloor inhabitants amongst the most abundant clone lineages; however, both geochemical analysis and microbial community structure reveal the borehole to be compromised by bottom seawater intrusion. Regardless, this study provides independent support for previous observations seeking to identify phylogenetic groups of microorganisms common to the deep ocean crustal biosphere, and extends previous observations by identifying additional lineages that may be prevalent in this unique environment.